Capability and Reversibility of LiCoO2 during Charge/Discharge with O3/H1−3 Layered Structure Change. Issue 5 (11th May 2021) - Yano, Akira; Taguchi, Noboru; Kanzaki, Hisao; Shikano, Masahiro; Sakaebe, Hikari
Abstract : The capability and reversibility of surface-coated LiCoO2 (LCO) during charge/discharge with a layered structure change between O3 and H1−3 phases was investigated. A compound oxide phase with a thickness of several nanometers and a LiMO2 structure (M: Co, Al, or Zr) formed on the surface of the coated LCO. The discharge capacity ( Q D ) and discharge energy density ( E D ) at a current-rate of 0.05 C in the initial charge/discharge voltage range of 2.5–4.6 V were 228 mAh g −1 and 936 Wh kg −1, respectively. The Q D at the 1st cycle at 1 C was 213 mAh g −1, and the retention at the 101st cycle was 88.8%. The Q D and E D at 6 C were 204 mAh g −1 and 778 Wh kg −1 . Operando XRD and impedance analyses revealed that the decrease in capacity by cycling was mainly due to the increased polarization, which was caused by the increase in the Li-ion intercalation resistance at the electrode/electrolyte interface. The O3/H1−3 phase transition was reversible even after the cycle-test. Most of the capacity in the O3/H1−3 transition region could be reversibly charged/discharged up to 100 cycles. The transition from H1−3 to O3 during discharging was responsive up to a current-rate of 6 C.